5-chloro-1H-indole-3-carbaldehyde benzoylhydrazone - Ali, Hapipah Mohd; Ng, S.W.; Xie, M.J.; Najwa, M.I. (International Union of Crystallography, 2006)
In the title compound, C16H12ClN3O, the amide O atom serves as an N-H center dot center dot center dot O hydrogen-bond acceptor to the amide and amine groups of two adjacent molecules, resulting in a layered structure.